Biopsychosocial factors associated to self-percepted sleep function in Brazilian elderly people: analysis of a national survey - Johnnatas Mikael Lopes; Angelo Giuseppe Roncalli
ABSTRACT: Background: Sleep is a dimension of well-being and health. Non-restful sleep is related to health dysfunctions, especially in vulnerable populations, considering that related factors change contextually. Thus, the objective of the present study was to measure the magnitude of the reduction in sleep restorative function (SRF) and related biopsychosocial factors in Brazilian elderly. Method: Secondary data from the 2013 National Health Survey of cross-sectional design were analyzed. The sample consisted of individuals as from 60 years old. The outcome considered was the prevalence of reduced self-perceived sleep restorative function (SRF). Health and sleep characteristics, emotional behavior, lifestyle, social support, and urbanization were all investigated. The association with outcome was measured with the prevalence ratio (PR) and estimated with Cox regression, assuming α ≤ 0.05. Results: SRF was reduced by 29.2% (95%CI 27.2 - 30.6%). It is related to depression (PR = 3.37; 95%CI 2.87 - 3.97), insomnia/sleepiness (PR = 2.45; 95%CI 2.14 - 2.79); behavioral oscillation (PR = 1.75; 95%CI 1.53 - 1.99), negative health perception (PR = 1.50; 95%CI 1.23 - 1.82), computer and internet (PR = 1.44; 95%CI 1.01 - 2.07) and functional difficulty (PR = 1.13; 95%CI 1.01 - 1.27). Living in urban areas (PR = 1.32; 95%CI 1.14 - 1.52) and having a chronic condition (PR = 1.58; 95%CI 1.11 - 2.40) were only associated to the worst situation of reduced SRF. Conclusion: The reduction in SRF affects one third of the elderly in Brazil and is closely related to biopsychosocial factors, requiring intersectoral public health promotion approaches.